The Factors Affect the Quality of Financial Statements Audit in Vietnam Businesses - Do Huu, Hai (Canadian Center of Science and Education, 2016)
The development of a market economy, especially the financial markets is asking for transparency and truthfulness of the financial information with high quality. The information in the financial statements will impact directly and indirectly to the rights and decisions of investors. Independent auditors play a role of evaluating truthfulness and reasonable financial information in enterprises, however there are still risks. This study focuses on analyzing the factors affecting the quality of financial statements audit in enterprises. The analytical methods used in this study are: factor analysis method to explore and test the Cronbach's alpha coefficient for the construction and testing of measuring scales. Moreover, linear structural modeling method (Structural Equation Modeling SEM) is used to test the reliability and value of discrimination, convergence, unitary of the concept and scale of research. The study results showed that occupational qualification is an important factor affecting the audit quality in the establishment of the business financial statements and legal environment factors, factors belonging to business, factor of independence, factors of quality control system of audit firm.